Implementing reflective journals to promote mental well-being in education - Kamarulzaman, Wirawani; Ibrahim, Hasniza; Abd Karim, Aishah Hanim (Asian Scholars Network, 2024)
With increasing concerns about university students' mental health, it is crucial to find methods that address both their academic progress and emotional well-being. One promising approach is reflective journaling, which gives students a structured way to express their feelings, build self-awareness, and support their mental health. Despite its potential, there is limited research on how students perceive reflective journaling and its effects on their mental well-being. This study explores the experiences of six undergraduate students from a public university who engaged in reflective journaling as part of their academic work. The interviews revealed that journaling encouraged positive thinking, improved self-awareness, provided a safe space for emotional expression, reduced anxiety and overthinking, enhanced control and perspective, and strengthened problem-solving abilities. The findings highlight that reflective journaling serves as both a learning tool and a mental health resource, helping students develop resilience and holistic growth. Further research could examine its use in various disciplines and design prompts tailored to specific challenges students face. Universities might integrate reflective journaling into their mental health strategies to better support students academically and emotionally.